On the Selective Use of Spectral Analysis - Percival, John (The Review of Economics and Statistics, 1975)
I have entirely avoided in this comment the important question of whether the empirical difficulties, especially correlation between pollution and unmeasured neighborhood characteristics, are so overwhelming as to render the entire method useless. I hope that with the air cleared of theoretical misconceptions, future work can proceed to solving these practical problems. For example, recent improvements in pollution measurements and in county assessors' data on individual homes might be combined to permit regressions within a more uniform area. The degree of attention devoted to this kind of detail is what will really determine whether the method stands or falls, once it is recognized that its theoretical underpinnings are sound.